P056 South Asian ethnicity drives differences in microbial and metabolic profiling in a newly diagnosed ulcerative colitis cohort. (16th January 2018) - Misra, R; Sarafian, M; Pechilvanis, A; Ding, N; Boulange, C; Marchesi, J; Holmes, E; Faiz, O; Arebi, N
Abstract: Background: The incidence of ulcerative colitis (UC) in South Asian (SA) migrants is higher than Caucasians. Ethnicity and migration cause changes in microbial profile. We examined microbial and metabolic profiles which may elucidate differing pathways in disease pathogenesis. Methods: Demographics, disease phenotype, treatment and disease severity using simple clinical colitis index (SCCAI) were recorded. Blood, urine, and faecal samples were collected at three time points over a 1 year period from newly diagnosed SA and Caucasian patients. We collected 102 urine, 78 serum, and 85 faecal samples from 23 SA and 15 Caucasian patients and 15 healthy controls. Nuclear magnetic spectroscopy (NMRS) and liquid-chromatography mass spectroscopy with bile acid and polar molecule (HILIC) profiling of metabolites was undertaken. 16S rRNA genes were sequenced on Illumina MiSeq platform. Patients completed a food frequency questionnaire at inclusion. Results: There were no significant differences in median age and disease phenotype. Mean SCCAI score was higher in SA (6.6 vs. 4.3). More SA were on steroid treatment at diagnosis (26% vs. 0%). There were significant differences between the groups in microbial profiling at phylum, family and genus levels (Figure 1) with overall lower diversity in the SA cohort by Chao 1 index. There were no significant differences in macronutrient or micronutrient dietary intake. Metabolic profiling revealed significant differences between SA and Caucasians across all biofluids and analytical platforms. Strongest models were faecal HILIC (R2X = 0.129, R2Y = 0.8, Q2Y = 0.596, p = 6.47 × 10 −5 ) and urine HILIC (R2X = 0.164, R2Y = 0.783, Q2Y = 0.526, p = 7.11 × 10 −12 ). Urinary NMRS showed higher isobutyrate, lactate and alanine in the SA group whilst hippurate, 4-cresol sulphate, lysine and citrate were reduced. Secondary bile acids (5B-cholanic acid-3a, 6a-diol-7-one) were higher in the SA group and four secondary bile acids (3-Ketocholanic acid, Lithocholic acid, Isolithocholic acid, 3a-hydroxy-12-ketolithocholic acid) were lower. There were no discriminatory features identified during time point and treatment subgroup analysis. Conclusions: This prospective, longitudinal inception cohort study demonstrates significant differences driven by ethnicity despite similar diet. SA had more severe disease which maybe a confounding factor. Analysis of paired samples pre- and post-remission are required. Further studies employing metagenomics techniques may define pro-inflammatory pathways specific to SA and justify different treatment approaches.